Capital and Closure in the EU Field. Advancement in the European Economic and Social Committee. (28th December 2021) - Johansson, Håkan; Uhlin, Anders; Arvidson, Malin
Abstract: This article explores what it takes to advance to the top of an EU institution (European Economic and Social Committee). The article combines Bourdieu's theories of field and capital with Weber's theory of social closure to study the interplay between required forms of capital and closure practices during three ideal‐typical phases of upward mobility: 'getting in', 'fitting in' and 'moving on'. Drawing on 26 semi‐structured interviews, the article finds that capital and closure are mutually interdependent as members' access to capital to advance depends on whether they pass the closure tests deployed by closure agents and manage to get in, fit in and move on in the EU field. By combining capital and closure approaches, the article suggests a new balance between structure and actor‐centred theories, which can help us better capture what is at stake in the EU field, and how the game of career advancement is played.